Comparison of Rates of Hospitalization Between Single and Dual Virus Detection in a Mexican Cohort of Children and Adults With Influenza-Like Illness. (3rd October 2019) - Noyola, Daniel E; Hunsberger, Sally; Valdés Salgado, Raydel; Powers, John H; Galindo-Fraga, Arturo; Ortiz-Hernández, Ana A; Ramirez-Venegas, Alejandra; Moreno-Espinosa, Sarbelio; Llamosas-Gallardo, Beatriz; Guerrero, M Lourdes; Beigel, John H; Ruiz-Palacios, Guillermo; et al.
Abstract: Background: Molecular detection methods allow for the simultaneous detection of several infectious agents. This study assesses whether co-infection with 2 viruses as compared with 1 is associated with increased hospitalization in those with acute respiratory infections. Methods: We prospectively enrolled a cohort of pediatric and adult participants with influenza-like illness during 2010–2014 in Mexico. Clinical information and respiratory samples were collected at enrollment. Respiratory viruses were detected with multiplex polymerase chain reaction (PCR) and influenza-specific reverse transcription PCR assays. Participants were followed for 14 and 28 days after inclusion. Severity of disease, as measured by hospitalization with acute respiratory infections, was compared between single and dual viral infections. Results: Among 5662 participants in the study, either 1 (n = 3285) or 2 (n = 641) viruses were detected in 3926 participants. Rhinovirus (n = 1433), influenza (n = 888), and coronaviruses (n = 703) were the most frequently detected viruses (either alone or in co-infection). Bocavirus, respiratory syncytial virus (RSV), metapneumovirus, and rhinovirus cases were hospitalized more often than other viruses. Bocavirus+rhinovirus cases were hospitalized more often than those with rhinovirus alone (but not bocavirus alone). RSV cases were more likely to be hospitalized than cases with co-infections of RSV and parainfluenza virus or coronavirus. Metapneumovirus cases were hospitalized more often than those co-infected with metapneumovirus+coronavirus. Conclusions: In this study, detection of 2 viruses did not significantly increase hospitalizations compared with single virus infections. Larger studies will allow for distinguishing between sequential and simultaneous infection and for a better understanding of the role of each virus during the evolution of acute respiratory episodes.